Physical Environment and Learning through Play: Case Studies in Malaysian Preschools - Lim, Pearly Pei Li; Bahauddin, Azizi (School of Social Sciences, USM, 2017)
As acquisition of knowledge includes the role of experience in acquiring knowledge, Learning through Play (LTP) becomes essential for children’s physical, social and cognitive development. LTP has also been identified as one of the teaching and learning approaches in Malaysia’s National Preschool Curriculum Standard (NPCS) to achieve its specified learning and development components. With physical environment capable of providing sensory stimuli and learning opportunities, physical environment aligned with the vision and principles of LTP should equally be given emphasis. This paper examines the physical environment of preschools in an attempt to demonstrate the relationship between LTP practices and a preschool’s physical environment. A case study research was undertaken based on a sampling frame with purposive homogeneous sampling employed to select four privately operated preschools within converted residential houses in Johor Bahru. Findings of qualitative analysis indicated that albeit physical environment of preschools are less supportive of LTP, children used ingenuity to modify and adapt their physical environment in support of their individual play needs. LTP was hindered due to lack of children’s own free will and accessibility to materials and equipment as well as constrained independent mobility and allowable play with restrictions imposed due to safety concern and time factor. Finally, conclusions are presented and suggestions for possible future direction are discussed.